Introduction to customized occupational safety and health website and its effectiveness in improving psychosocial safety climate (PSC) among police officers - Rasdi, Irniza; Ismail, Nadia Farhana; Kong, Andy Shin Shyen; Muhamad Saliluddin, Suhainizam (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: The prevalence of stress among Malaysian police is high in which 38.8% polices have severe stress related to work resources and workplace environment. Psychosocial safety climate is one of the indicators that can be used to avoid psychosocial health problems. Objective: This study was conducted to determine the risk factors of psychosocial safety climate and to measure the effectiveness of a customised safety website in improving the safety climate. Methodology: This study involved 105 police officers who were randomly selected from nine different departments in PDRM Bukit Aman. A survey adapted from previous study was used to determine the psychosocial safety climate levels among respondents. Then, occupational safety website was introduced to the respondents and being used for two weeks. Lastly, post survey was done to see the difference of psychosocial safety climate before and after the use of the website. Results and Discussion: Findings showed that team psychological safety (r=0.381, p=<0.001) and physical safety climate (r=0.657, p=<0.001) were significantly associated with psychosocial safety climate level. The means before (36.095 ± 5.6202) and after (37.742 ± 4.7069) the introduction of occupational safety website was good. Still, there was a significant improvement of psychosocial safety climate level after the introduction of occupational safety website. Conclusion: This study showed that psychosocial safety climate level in an organization can be improved by introducing an informative website specific for police.